Empowerment of a Community-Based Coffee Shop to Develop an Entrepreneurial Ecosystem through Collaboration with Stakeholders - Priyono, Anjar; Moin, Abdul; Piper, Ivan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the role of a community-based coffee shop as an entrepreneurial ecosystem that serve as the hub for economic activities among local citizens. Utilizing an action research approach, the community service team engaged directly in the field, facilitating the coffee shop’s collaboration with various stakeholders to foster value creation. The team worked closely with stakeholders to establish an entrepreneurial ecosystem within the coffee shop venue, aiming to actualize co-value creation. In this context, value creation is collaborative among ecosystem participants and is not merely linear; the coffee shop cannot simply offer products and expect customers to visit. The enhancement of community economic well-being is evidenced by increased economic activity around the coffee shop area.